Day 3 Wed, January 15, 2020 2020
DOI: 10.2523/iptc-20282-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Viscosity Acid Platform: Benchmark Study Reveals Superior Reaction Kinetics at Reservoir Conditions

Abstract: Stimulation of carbonate reservoirs using suitable acid systems is common practice to alleviate damage caused by the drilling and completion operations and to increase permeability by way of acid fracturing operations in tight formations. This process creates conductive channels in the pay zone allowing for oil and gas recovery. Several drawbacks however can be encountered, particularly at elevated temperatures, when using strong mineral acids, i.e., hydrochloric acid (HCl). Under these harsh conditions, propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Understanding reaction kinetics between the rock and acid is necessary to optimize the acidizing process. The rotating disk apparatus (RDA) has been used to study reaction kinetics between rocks and Newtonian and non-Newtonian fluids (Hansford and Litt 1968;Boomer et al 1972;Lund et al 1973;Roberts and Guin 1975;Prakongpan et al 1976;Anderson 1991;Fredd and Fogler 1998;Alkattan et al 1998;Conway et al 1999;Taylor and Nasr-El-Din 2009;Rabie et al 2014;Li et al 2016;Liao et al 2017;Abdelgawad et al 2018;Kotb et al 2018;Sayed et al 2020). However, no standard exists in the literature for the acid volume used in RDA experiments.…”
Section: Newtonian Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding reaction kinetics between the rock and acid is necessary to optimize the acidizing process. The rotating disk apparatus (RDA) has been used to study reaction kinetics between rocks and Newtonian and non-Newtonian fluids (Hansford and Litt 1968;Boomer et al 1972;Lund et al 1973;Roberts and Guin 1975;Prakongpan et al 1976;Anderson 1991;Fredd and Fogler 1998;Alkattan et al 1998;Conway et al 1999;Taylor and Nasr-El-Din 2009;Rabie et al 2014;Li et al 2016;Liao et al 2017;Abdelgawad et al 2018;Kotb et al 2018;Sayed et al 2020). However, no standard exists in the literature for the acid volume used in RDA experiments.…”
Section: Newtonian Fluidsmentioning
confidence: 99%
“…The theory of an RD was first applied to study the electrochemical processes using an RDE (Daguenet 1968;Ellison et al 1971;Chin and Litt 1972;Nanis and Klein 1972;Vahdat and Newman 1973;Bruckenstein and Miller 1977;Mohr and Newman 1976;Albery and Bruckenstein 1983;Dong et al 2008), and was later adopted to analyze the chemical dissolution reactions using RDA (Boomer et al 1972;Lund et al 1973, Lund et al 1975Fredd and Fogler 1998;Taylor et al 2004;Alkhaldi et al 2010;Rabie et al 2014;Khalid et al 2015;Aldakkan et al 2018;Hall-Thompson et al 2020;Sayed et al 2020;Kotb et al 2021).…”
Section: Turbulence In the Rotating Disk Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of temperature on the acid rock interaction between a calcite rock and a low-viscous acid system (LVAS-1) (a pre-engineered mixture of HCl and organic acid) was conducted using RDA by Sayed et al 106 At different temperatures of 180, 300, and 350 °F, the acid diffusion coefficients were determined. The results indicated that an increase in the temperature of the system increased the acid diffusion coefficient.…”
Section: Annular Flow Reactormentioning
confidence: 99%
“…Experimental work in the core flooding setup was first conducted to understand the parameters that control the acidizing in carbonate rocks. These experimental studies analyzed the impact of rock properties, injection conditions, pressure, mineralogy, temperature, and reaction kinetics on the created channels. In those linear core flooding experimental studies, the acidic solution is injected at a different rate in a cylindrical core sample, and the pore volume to the breakthrough was measured along with the other pressure measurements. ,, …”
Section: Introductionmentioning
confidence: 99%